Do patients with diabetic nephropathy arrive on time to the Nephrology Service in Cayetano Heredia Hospital? A one-year assessment: January 2011-January 2012 - Loza Munarriz, Cesar (2013)
Diabetic nephropathy has been reported in Peru as the first cause for end-stage kidney disease; and secondary prevention cannot not take place because of patients coming so late for their first nephrology assessment. Objectives: To determine the proportion of patients with diabetic nephropathy who come on time for their first nephrology assessment in Cayetano Heredia Hospital. Material and Method: We obtained demographic, clinical, and laboratory data from 73 patients diagnosed with type 2 diabetes mellitus between January 2011 and January 2012. We describe rates and proportions. Results: Of these 73 patients assessed, 50 (68,49%) arrived with advanced kidney disease to the nephrology outpatient clinic (diabetic nephropathy, Mogensen stages IV and V), stage IV was the most frequent presentation, it was found in 47 patients (64,38%), and 3 (4,11%) arrived to the clinic with stage V diabetic nephropathy. Only 7 patients (9,59%) arrived in stage II, and no stage I patient ever arrived to the hospital. Twelve patients (92,31%) were referred from the Emergency Department. Mean creatinine clearance values were 59,24 ± 43 cc/min x 1,73 m2 body surface area (1,86-293). Proteinuria values were 2,353 ± 3,291 g/24 hours, within this range (29-15103 g), and 43 (61,43%) patients showed significant proteinuria, 14 (20%) had massive proteinuria, and 3 (4,29%) were considered to have malignant proteinuria. Conclusions: Most diabetic nephropathy patients in this report arrive late to the nephrology outpatient clinic, most frequently presenting with advanced kidney disease.